Noninvasive molecular imaging of apoptosis in vivo using a modified firefly luciferase substrate, Z-DEVD-aminoluciferin - Hickson, J; Ackler, S; Klaubert, D; Bouska, J; Ellis, P; Foster, K; Oleksijew, A; Rodriguez, L; Schlessinger, S; Wang, B; Frost, D (Cell death and differentiation, 2010)
Apoptosis is a highly regulated process of programmed cell death essential for normal physiology. Dysregulation of apoptosis contributes to the development and progression of various diseases, including cancer, neurodegenerative disorders, and chronic heart failure. Quantitative noninvasive imaging of apoptosis in preclinical models would allow for dynamic longitudinal screening of compounds and facilitates a more rapid determination of therapeutic efficacy. In this study, we report the in vivo characterization of Z-DEVD-aminoluciferin, a modified firefly luciferase substrate that in apoptotic cells is cleaved by caspase-3 to liberate aminoluciferin, which can be consumed by luciferase to generate a luminescent signal. In two oncology models, namely SKOV3-luc and MDA-MB-231-luc-LN, at 24, 48, and 72 h after treatment with docetaxel, animals were injected with Z-DEVD-aminoluciferin and bioluminescent images were acquired. Significantly more light was detected at 24 ( P <0.05), 48 ( P <0.01), and 72 h ( P <0.01) in the docetaxel-treated group compared with the vehicle-treated group, with caspase-3 activation at these time points confirmed using immunohistochemistry. Importantly, whereas significant differences between groups were detected as early as 24 h after treatment by molecular imaging, caliper measurements were unable to detect a difference for 4–5 additional days. Taken together, these data show that in vivo imaging of apoptosis using Z-DEVD-aminoluciferin could provide a sensitive and rapid method for early detection of drug efficacy, which could potentially be used by numerous therapeutic programs.